Exploring Fe–Mn–Al–C lightweight steels via in-situ alloying in direct energy deposition - Seungjin Nam; Chahee Jung; Hyun Chung; Heechan Jung; Young Mok Kim; Hyoung Seop Kim; Hyunjoo Choi; Seok Su Sohn (Journal of Materials Research and Technology)
This study explores the feasibility of in-situ alloying via direct energy deposition (DED) to tailor microstructures and strength-ductility balance of Fe–Mn–Al–C lightweight steels (LWSs) with independently varied composition of 8–12 wt% Al and 20–25 wt% Mn. As the Al content increased, the matrix phase was transformed from austenitic (8Al) to ferritic (10Al and 12Al), accompanied by the formation of secondary phases. The in-situ alloyed LWSs exhibited a reduced density (6.5–7.0 g/cm3) while exhibiting an exceptional strength-ductility synergy. Specifically, 20Mn8Al LWS exhibited an ultimate tensile strength of 883 MPa and an elongation of 43.8 %, resulting in a product of strength and elongation of 39 GPa∙%. It also achieved a weight reduction of 10 % compared to conventional stainless steel. Strengthening was primarily governed by pre-existing dislocations and solid-solution strengthening effects, while deformation twinning in 20Mn8Al enhanced strain hardening and delayed necking. These findings highlight the potential of in-situ alloyed LWSs for lightweight structural applications, offering a superior combination of mechanical properties and density reduction. Furthermore, this study establishes DED-based in-situ alloying as a versatile strategy for microstructural and mechanical property optimization in additive manufacturing of advanced steels.